A selection of frescoes in the tombs of Bagwat region from the first to the sixth centuries AD - Rana Basheer (Maǧallaẗ Al-Turāṯ wa Al-Taṣmīm, 2023)
Bagwat tombs are one of the oldest gatherings of Christian cemeteries in Egypt and a witness to an important transitional stage in the history of El Kharga Oasis in the Western Desert, which is the Roman period until the advent of Christianity and then considering it the official religion of the Roman Empire, of which Egypt was one of its provinces at that time and during that period an art differed in its essence and its artistic style from the classical art that was prevalent in the art scene at this time, and the walls of Bagwat tombs contains drawings expressing that artistic stage and its development.This research, which is based on the field study and the descriptive analytical method, deals with the analysis of the technical characteristics of the frescoes in the Bagawat tombs and the most important factors that effected the production of murals from historical factors that led to the emergence of Coptic art and Byzantine art in Egypt and the distinctive characteristics of those arts and the characteristics of architecture in the Bagawat tombs and the most important distinctive architectural elements and the impact of the environment factor on the architecture of the Bagawat tombs and the characteristics of the frescoes by describing and analyzing the illustrated themes, the artistic style in which they were painted, the artists who implemented these murals, the most important results and recommendation of the study.